Controversial issues in comorbidity between epilepsy and autism: subclinical epileptiform activity and autistic epileptiform regression - G. V. Kuzmich; A. N. Sinelnikova; K. Yu. Mukhin (Русский журнал детской неврологии, 2019)
Early childhood autism, or autism spectrum disorders, is an extremely heterogeneous group of conditions that share similar symptoms of dysontogenesis. The most significant comorbidity in patients with autism is epilepsy, which is still associated with a variety of controversies. The present article covers the most controversial aspects of comorbidity between autism and epilepsy, including the impact of psychopharmacotherapy on the risk of epilepsy, clinical significance of epileptiform activity on the electroencephalogram in patients without epilepsy, and criteria for and prevalence of autistic epileptiform regression syndrome. We found that there is still a lack of reliable evidence for the majority of issues related to the combination of autism and epilepsy. We emphasize the need for further studies. We also provide a detailed description of the history, criteria, prevalence, and clinical examples of autistic epileptiform regression syndrome.